Giving Nuggets (Libertry) of Brocoly, Eel, Anchor, Against the Growth of Stunting Children in 2019 - Niasty Lasmy Zaen; Dewi Ramadani Buulolo; Nila Hayati (Institute of Computer Science (IOCS), 2020)
Stunting is a major nutritional problem that will have an impact on social and economic life in society. There is clear evidence that individuals who are stunted have a higher mortality rate. Stunting will affect physical work performance and mental and intellectual functions will be impaired (Mann and Truswell, 2012). This is also supported by Jackson and Calder (2004) who state that stunting is associated with impaired immune function and increases the risk of death. So that high protein is needed to stimulate the growth of toddlers with stunting by using foods that have high protein such as anchovies, eels and broccoli. Food and nutrition are factors that are closely related to efforts to improve the quality of human resources. People who have fulfilled their needs with balanced nutritional quality are better able to participate in development. Food and nutrition problems are complex problems and are interrelated with one another. Several approaches are used in determining food and nutritional status assessments by assessing consumption and eating habits as well as assessing the nutritional status of a particular area or group. Each region has food and nutrition problems that are different from other regions. The area where the population lives also determines the consumption pattern of the community (Augustyn, 2002). To fulfill the dietary pattern of children under five requires an innovation in research to fulfill the nutrition of children in the form of naget (libertri) giving programs, namely broccoli, anchovies and eels. The research objective was to identify whether giving nuggets could increase the growth of toddlers with stunting. Research method using quasi experiment Research results There was a significant difference in the mean z-score of TB / U before and after treatment in the group given the libertarian nugget, with a p-value of 0.000 (p <0.05). There was a significant difference in the growth of stunting children who were given nuggets and those who were not given nuggets. The increase in the nutritional status of toddlers from very short to short and from short (stunting) to normal, namely 36%. Meanwhile, in the control group there was an increase of 4%.